A case of Hashimoto's encephalopathy presenting with seizures and psychosis - Min-Joo Lee; Hae-Sang Lee; Jin-Soon Hwang; Da-Eun Jung (Korean Journal of Pediatrics, 2012)
Hashimoto's encephalopathy (HE) is a rare, poorly understood, autoimmune disease characterized by symptoms of acute or subacute encephalopathy associated with increased anti-thyroid antibody levels. Here, we report a case of a 14-year-old girl with HE and briefly review the literature. The patient presented with acute mental changes and seizures, but no evidence of infectious encephalitis. In the acute stage, the seizures did not respond to conventional antiepileptic drugs, including valproic acid, phenytoin, and topiramate. The clinical course was complicated by the development of acute psychosis, including bipolar mood, insomnia, agitation, and hallucinations. The diagnosis of HE was supported by positive results for antithyroperoxidase and antithyroglobulin antibodies. Treatment with methylprednisolone was effective; her psychosis improved and the number of seizures decreased. HE is a serious but curable, condition, which might be underdiagnosed if not suspected. Anti-thyroid antibodies must be measured for the diagnosis. HE should be considered in patients with diverse neuropsychiatric manifestations.